2018
DOI: 10.1007/s13593-018-0524-4
|View full text |Cite
|
Sign up to set email alerts
|

Questioning the work of farmers, advisors, teachers and researchers in agro-ecological transition. A review

Abstract: The French Ministry of Agriculture has called for agro-ecological transitions that reconcile farming and the environment. In this review, we examine the transformations of farmers and AKIS (Agriculture Knowledge Innovation System) actors' work during agro-ecological transitions, and argue that the content, organization, and aim of farmers' work are influenced by agricultural training, agricultural development, and discussions between peers, research, and regulations. Our main findings concern those transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 32 publications
1
26
0
8
Order By: Relevance
“…Before or during the experiment on his/her farm?" Several authors have shown that field testing the new practice is a key stage of the change of practice (Collerette et al 1997;Chantre 2011;Toffolini et al 2016;Catalogna et al 2018). For each farmer interviewed, we identified and categorized the work-related changes, and for each category, we identified the various information items the farmers had used in connection with it.…”
Section: Qualitative Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Before or during the experiment on his/her farm?" Several authors have shown that field testing the new practice is a key stage of the change of practice (Collerette et al 1997;Chantre 2011;Toffolini et al 2016;Catalogna et al 2018). For each farmer interviewed, we identified and categorized the work-related changes, and for each category, we identified the various information items the farmers had used in connection with it.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…But he also said it was always different from one farm to another, and that it was by experimenting and seeking solutions to problems as they arose that one could gradually reorganize the work, i.e., "who does what when," depending on each year's weather conditions. Several authors have identified innovation experiments as the key stage in the process of changing to a new practice (e.g., Collerette et al 1997;Chantre 2011;Toffolini et al 2016;Catalogna et al 2018).…”
Section: Innovation Experimentation As the Key Stage For Information Usementioning
confidence: 99%
See 1 more Smart Citation
“…Un partage des pistes de recherches devient envisageable et des chantiers méthodologiques communs, entre systèmes d'élevage et de cultures, pourraient porter par exemple sur les aléas dans la réalisation des travaux de saison, l'optimisation de la délégation, les conséquences de la robotisation, etc. (Coquil et al, 2018). En prolongeant les tendances actuelles Gambino et al (2012) décrivent un portrait social prospectif des agriculteurs, marqué, entre autres, par l'affaiblissement du particularisme du secteur, qui peut induire des pertes d'identité professionnelle mais aussi susciter de nouvelles synergies.…”
Section: Des Expériences Utiles à D'autres Secteursunclassified
“…D'autres moteurs sont à l'origine des évolutions des métiers d'éleveur. Ainsi, les injonctions sociétales à « produire autrement » (Coquil et al, 2018) modifient les pratiques agricoles et les évolutions sociales interpellent de manière réflexive le mode de vie des familles (Fillonneau, 2012).…”
Section: Introductionunclassified